2017
DOI: 10.3329/akmmcj.v7i1.31611
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Oral Health Literacy Level Among Bangladeshi Adults Seeking Dental Care and Its Relationship With Socio-demographic Characteristics

Abstract: Background: The important role of socio-economical factors in oral health and disease has been identified. Oral health literacy is associated with inaccurate knowledge about preventive measures such as proper brushing, dental care visits and oral health-related quality of life. Like general health literacy, oral health literacy incorporates the capacity a person has to learn and use information about oral health in making decisions about their oral health. Objective: This analytic type of cross sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
5
6
0
Order By: Relevance
“…This study’s findings about the OHL of parents—inadequate level 43.9%, marginal level 24.8%, and adequate level 31.3%—are in agreement with a study conducted among the Brazilian population by Firmino et al [ 30 ], where the OHL level of the participants was found to be inadequate (37%), and also among the Iranian population, where more than half of the participants had an inadequate and marginal (55.7%) OHL level [ 31 ]. Furthermore, in agreement with our study, the OHL level of participants was found to be inadequate or poor (49%) among the Bangladeshi population [ 32 ] and among the Indian population, where 35% of participants had an inadequate OHL level [ 33 ]. An inadequate level of OHL has been found in various studies and is consistent, possibly because of low education levels, people living in rural areas, ethnic minorities, and low socioeconomic status among the studied populations [ 30 , 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study’s findings about the OHL of parents—inadequate level 43.9%, marginal level 24.8%, and adequate level 31.3%—are in agreement with a study conducted among the Brazilian population by Firmino et al [ 30 ], where the OHL level of the participants was found to be inadequate (37%), and also among the Iranian population, where more than half of the participants had an inadequate and marginal (55.7%) OHL level [ 31 ]. Furthermore, in agreement with our study, the OHL level of participants was found to be inadequate or poor (49%) among the Bangladeshi population [ 32 ] and among the Indian population, where 35% of participants had an inadequate OHL level [ 33 ]. An inadequate level of OHL has been found in various studies and is consistent, possibly because of low education levels, people living in rural areas, ethnic minorities, and low socioeconomic status among the studied populations [ 30 , 31 , 32 , 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, in agreement with our study, the OHL level of participants was found to be inadequate or poor (49%) among the Bangladeshi population [ 32 ] and among the Indian population, where 35% of participants had an inadequate OHL level [ 33 ]. An inadequate level of OHL has been found in various studies and is consistent, possibly because of low education levels, people living in rural areas, ethnic minorities, and low socioeconomic status among the studied populations [ 30 , 31 , 32 , 33 ]. Our study results revealed a higher inadequate level of OHL among parents with primary school qualifications and among unemployed parents, which shows that education and employment are important factors for good OHL levels.…”
Section: Discussionsupporting
confidence: 89%
“…Only about 40% of respondents agree that utilization of telemedicine has increased in their daily internet usage, and only about one-third of the respondents have used the internet for aid regarding the COVID-19 pandemic. These low numbers are due to a combination of issues: poor knowledge about the systems of telemedicine, habitual biases towards face-to-face healthcare [ 58 ], poor ICT culture among health professionals [ 59 ], lack of trained health staff, low health literacy [ 60 ], and also a lack of a robust digital security law imposed on telemedicine systems of Bangladesh to protect the data of users. Combining these three statistic ideas presented can help health analysts figure out ways to increase these numbers for a better future in healthcare and its related economics.…”
Section: Discussion and Future Considerationmentioning
confidence: 99%
“…34 Appropriate data about health literacy are not available; however, a study conducted in 2017 found that 7% of respondents had very poor, 49% had poor and 41% had fair oral health literacy level. 35 Limited health and digital health literacy are well described as barriers to getting optimal clinical service.…”
Section: Low Health Literacymentioning
confidence: 99%